Russische Institutionen des 19. Jhs und der Akademiker Avgust Karlovič Nauck - Gavrilov, Alexander (Hyperboreus, 2014)
Examining the case of the outstanding academician August Nauck, the author deals with the role of ofﬁcial institutions in the history of Classical scholarship and Classical education in Russia. Nauck had never been a professor of the University of St Petersburg. He combined a tremendous amount of research work with teaching at the St Petersburg Institute for History and Philology (training school teachers), attempts at improving the system of school education, editorial activities and even compiling a catalogue for the Library of the Academy of Sciences.